Learning Community on Computer-Based Statistics Acceptance for Accounting Students - Hafsah, Hafsah; Sagala, Gaffar Hafiz; Ramdhansyah, Ramdhansyah (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
This study aims to examine the influence of the learning community on computer-based statistic acceptance. Acceptability is measured with perceived usefulness variables, perceived ease of use, perceived enjoyment, and reuse intention. This study used quasi-experimental design. To selecting the respondents, researchers used cluster random sampling and a questionnaire to collect the data. Respondents consisted of 207 accounting students of which 86 were engaged in the learning community while 121 were not. One-way ANOVA analysis result showed that students who participated in the learning community have better computer-based statistic acceptance than the students who did not. The learning community was found to be able to facilitate the transfer of knowledge among students more freely than in the classroom. Further research can consider true-experimental design or lab experiment with more rigorous manipulation for controlling bias from another variable that may consist.